The new geography of jobs - Moretti, Enrico (New York, 2013)
" "A persuasive look at why some U.S. cities have prospered in recent decades while others have declined."--"Bloomberg Businessweek " We're used to thinking of the United States in opposing terms: red versus blue, haves versus have-nots. But today there are three Americas. At one extreme are the brain hubs--cities like San Francisco, Boston, and Durham--with workers who are among the most productive, creative, and best paid on the planet. At the other extreme are former manufacturing capitals, which are rapidly losing jobs and residents. The rest of America could go either way. For the past thirty years, the three Americas have been growing apart at an accelerating rate. This divergence is one the most important developments in the history of the United States and is reshaping the very fabric of our society, affecting all aspects of our lives, from health and education to family stability and political engagement. But the winners and losers aren't necessarily who you'd expect. Enrico Moretti's groundbreaking research shows that you don't have to be a scientist or an engineer to thrive in one of the brain hubs. Carpenters, taxi-drivers, teachers, nurses, and other local service jobs are created at a ratio of five-to-one in the brain hubs, raising salaries and standard of living for all. Dealing with this split--supporting growth in the hubs while arresting the decline elsewhere--is the challenge of the century, and "The New Geography of Jobs "lights the way. "Moretti has written a clear and insightful account of the economic forces that are shaping America and its regions, and he rightly celebrates human capital and innovation as the fundamental sources of economic development."--Jonathan Rothwell, The Brookings Institution"